AN APPROACH OF ECOLINGUISTIC IN MINYAK KARO BASED ON ETHNOBOTANY - Karisma Erikson Tarigan; Dwi Widayati (Nusantara Hasana Journal, 2021)
This study proved the interrelated concepts of Minyak Karo based on biological, ideological, and sociological dimensions in Padang Bulan and Pancur Batu regency, North Sumatra. This study was in the form of descriptive qualitative study. The results proved that the ingredients to make Minyak Karo were cooking oil, green coconut oil, hundred spices, kaffir lime/kaffir lime leaves, panglai, kencur, shallots, garlic, pepper, nutmeg, nest wallet, ship leaves, jambar api, tawan gegeh, fresh ipuh, bulung patchouli , gagaten tiger, root areca nut, root riman, root bamboo, reeds, root pengkih, root palm, basil, tawan gegeh, turmeric and areca nut. The plant parts used in traditional medicine of Minyak Karo were leaf, root, rhizome, flower, stem, fruit, bark, seed, tuber, and latex in biological dimension. In ideological dimensions, Minyak Karo had the content of chant to invite the spirits of the ancestors. Based on sociological dimension, the purpose of the ritual of making Minyak Karo was to cure diseases that were believed to come from supernatural spirits or diseases sent by people through supernatural means and asked for protection from the spirits of the ancestors.